International common-carrier transportation industry and the competitiveness of the foreign trends of the countries of Latin America and the Caribbean (ECLAC SantiagoCL, 1989)
Looks at aspects such as structural changes in the liner shipping industry; in inland transport; in international commercial relations and the impact of changes in transport; in Latin American economic policies and their relations with the liner shipping industry; and the need for a response by Latin America and the Caribbean to ensure the competitiveness of their exports.
DC